Modelos pedagógicos que se aplican en la Institución Educativa Fiscal Ricardo Rodríguez ubicada en el sector de Pifo - Lita Heredia, Katherine Lizbeth (2018)
The purpose of this research is to identify the pedagogical models that are applied in the Ricardo Rodríguez Fiscal Educational Institution with the fifth year students of Basic General Education, in such a way that part of the description of the teaching task on the professional practice of the process teaching-learning, which highlights the use of teaching materials, methodologies, evaluation among other aspects, and it should be stressed that this case analysis is proposed for the purpose of the Titration Unit of the Universidad Polytechnic Salesiana. Therefore, the professional practice of the educators in the classrooms was directly evidenced, for this the Fundamentals of Basic Education were considered, the pedagogical models that the teachers used to teach their classes, and consecutively compare with the pedagogical model proposed by the teachers. The 2016 curriculum. Likewise, a theoretical framework is presented that supports the pedagogical models, foundations of education and the pedagogical model proposed by the 2016 curriculum. Next, the analysis of results, conclusions and recommendations of this research, previously structured by means of information collected through the direct observation sheet of the classes, field diary and interviews with teachers.